The Economic Impact of Non-communicable Disease in China and India: Estimates, Projections, and Comparisons - David E. Bloom; Elizabeth T. Cafiero; Mark E. McGovern; Klaus Prettner; Anderson Stanciole; Jonathan Weiss; Samuel Bakkila; Larry Rosenberg (Institute for the Study of Labor (IZA), 2013)
This paper provides estimates of the economic impact of non-communicable diseases (NCDs) in China and India for the period 2012-2030. Our estimates are derived using WHO's EPIC model of economic growth, which focuses on the negative effects of NCDs on labor supply and capital accumulation. We present results for the five main NCDs (cardiovascular disease, cancer, chronic respiratory disease, diabetes, and mental health). Our undiscounted estimates indicate that the cost of the five main NCDs will total USD 27.8 trillion for China and USD 6.2 trillion for India (in 2010 USD). For both countries, the most costly domains are cardiovascular disease and mental health, followed by respiratory disease. Our analyses also reveal that the costs are much larger in China than in India mainly because of China's higher income and older population. Rough calculations also indicate that WHO's Best Buys for addressing the challenge of NCDs are highly cost-beneficial.
Keywords: E13; I15; O40; 330; health and economic development; non-communicable disease; growth models; cost-effectiveness; Krankheit; Sterblichkeit; Gesundheitskosten; Makroökonomischer Einfluss; Wirtschaftswachstum; Alternde Bevölkerung; Prognose; Indien; China